Right–left digit ratios, a novel form of asymmetry: Patterns of instability in children and relationships to platelet counts and hospitalization in adults with COVID-19 - Kasielska-Trojan, Anna; Manning, John T.; Jabłkowski, Maciej; Białkowska-Warzecha, Jolanta; Kwasniewska, Oliwia; Hirschberg, Angelica L.; Antoszewski, Bogusław (Frontiers in Public Health, 2022)
High right minus left (R-L) asymmetry of digit ratios has been reported to be linked to hospitalization for COVID-19. Here we examined the developmental patterns of this novel form of asymmetry in children and further explored their relationships to platelet counts and hospitalization for COVID-19 in adult patients. We considered ratios calculated from four digits (2D, 3D, 4D, 5D) in: (i) a sample of healthy participants aged 2 years to 18 years (n = 680, 340 males) and (ii) 96 adult patients (42 males) hospitalized for COVID-19 and 100 controls (53 males). The protocol for (ii) included a questionnaire and laboratory test results. In sample (i) of the six unsigned digit ratio asymmetries, those which included 5D had the highest mean asymmetry with the greatest between-individual variation and they were unstable over the age range of 2 years to 18 years. In sample (ii) patients showed higher asymmetries than controls in four ratios (2D:4D, 2D:5D, 3D:5D, 4D:5D) and a sum of asymmetries of the two independent ratios (2D:4D+3D:5D) correlated positively with platelet counts and hospitalization. Conclusion: Means and SDs of digit ratio asymmetry that include the 5th digit are high and age-unstable. Digit ratio asymmetry, particularly 5th digit ratio asymmetry and a composite measure of 2D:4D + 3D:5D asymmetry, may be positively linked to high platelet counts in COVID-19 patients and to an elevated risk of hospitalization.